The correlation between rapid eye movement sleep behavior disorder and the progress of Parkinson’s disease: a systematic review and meta-analysis - Zheng, Wentao; Pan, Yang; Li, Kunhua; Tao, Keyu; Wang, Qiuyu; Yang, Yungui (Frontiers in Aging Neuroscience, 2024)
Background: This meta-analysis was conducted to evaluate potential differences in symptoms between PD patients with or without RBD. Methods: A systematic search was conducted in PubMed, Cochrane, Embase, and Web of Science databases (as of August 16, 2023), to identify relevant studies on PD and RBD. Statistical analysis was performed using Stata 15.0. Continuous variables were analyzed using the standardized mean difference (SMD) and 95% confidence interval (95% CI), while count data were assessed using the odds ratio (OR) and 95% CI as statistical effect sizes. Heterogeneity among all included studies was tested; for studies with low heterogeneity (I² < 50%), a fixed-effects model was used to calculate statistical results. For studies with relatively high heterogeneity (I² > 50%), a random-effects model was applied, followed by sensitivity and subgroup analyses to identify sources of heterogeneity. Results: A total of 5,672 subjects were involved in this study. Compared to the NRBD group, the UPDRS-III score in the RBD group was significantly higher (SMD = 0.20, 95% CI: [0.11, 0.29], P < 0.001), and the Hoehn-Yahr score in the RBD group was also significantly higher (SMD = 0.29, 95% CI: [0.03, 0.55], P < 0.001). Patients with PD in the RBD group had more severe cognitive impairments than those in the NRBD group (SMD = -0.30, 95% CI: [-0.48, -0.11], P < 0.001). The incidence of hallucination in PD patients in the RBD group was 3.0 times that of the NRBD group (OR = 3.0, 95% CI: [2.15, 4.20], P = 0.110). PD patients in the RBD group also experienced more severe anxiety symptoms (SMD = 0.13, 95% CI: [-0.26, 0.51], P < 0.001), had higher scores in depression scales (SMD = 0.22, 95% CI: [0.02, 0.43], P < 0.001), and higher scores in sleep disorder scales than those in NRBD group (SMD = 0.10, 95% CI: [-0.11, 0.31], P < 0.001). Conclusion: Results show PD patients with co-occurring RBD have more severe motor and non-motor symptoms likely due to overlapping affected regions in RBD and PD-related pathology, plus broader neurodegeneration seen in PD patients with RBD.